Assistive technology for children with learning disabilities: a systematic literature review - Abd Khalid, Ahmad Haiqal; Mohkhlas, Nur Nazihah; Zakaria, Noor Azura; Mat Rejab, Mazidah; Abdul Karim, Ruwinah; Suharsiwi, Suharsiwi (IEEE, 2023)
The enhancement of technology is well-developed and assistive technology is one of the foremost that has been used significantly. Individuals with disabilities use assistive technology to perform the desired activity that would otherwise be difficult or impossible. Mobility devices such as walkers and wheelchairs, as well as hardware, software, and peripherals that assist people with disabilities in accessing computers or other information technologies, are examples of assistive technology. Learning disabilities are caused by genetic and neurobiological factors that affect brain functioning, influencing one or more cognitive processes related to learning. This paper discusses a comprehensive systematic literature review (SLR) of the assistive technology (AT) for children with learning disabilities with combination of Kitchenham and PRISMA approach. This paper discusses on the assistive technologies developed for children with learning disabilities according to its type, purposes, techniques used, and platform or delivery system used to host the developed assistive technologies for children with learning disabilities.